2012
DOI: 10.1177/0194599812446913
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Viscoelastic Properties of Rabbit Vocal Folds after Implantation of Hyaluronic Acid‐Based Biomaterials

Abstract: HA-based biomaterials could preserve the viscoelastic properties of the vocal folds, when they were injected into vocal folds in an in vivo rabbit model. However, further studies on the influence of the biomaterials on the viscoelasticity of human vocal folds in ECM surroundings are still needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Vocal folds injected with hyaluronic acid based materials showed the lowest dynamic viscosity η’ values and were similar to non-injected control samples [49, 50]. Likewise, Choi et al found no significant difference in the elastic shear modulus G’ and viscous shear modulus G” in rabbit vocal folds injected with hyaluronan-based material versus non-injected controls [51]. Together, these studies demonstrate that HA substances may be appropriate for preserving or restoring vibratory capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Vocal folds injected with hyaluronic acid based materials showed the lowest dynamic viscosity η’ values and were similar to non-injected control samples [49, 50]. Likewise, Choi et al found no significant difference in the elastic shear modulus G’ and viscous shear modulus G” in rabbit vocal folds injected with hyaluronan-based material versus non-injected controls [51]. Together, these studies demonstrate that HA substances may be appropriate for preserving or restoring vibratory capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Dissected VFs were stored in normal saline at 37–C for 1 to 2 hours before viscoelastic measurements were taken. Functional rheometric evaluation was performed as previously described in our article . Viscoelastic parameters, such as elastic modulus ( G ′) and viscous modulus ( G″) , were calculated as functions of applied frequency according to the theory of linear viscoelasticity.…”
Section: Methodsmentioning
confidence: 99%
“…Functional rheometric evaluation was performed as previously described in our article. 19 Viscoelastic parameters, such as elastic modulus (G 0 ) and viscous modulus (G 00 ), were calculated as functions of applied frequency according to the theory of linear viscoelasticity. Dependence of viscoelastic parameters on frequency can be parameterized by the power law, G 0 or G 00 5 ax b , in which the coefficient a indicates magnitude and the constant b indicates slope on a log-log scale.…”
Section: Functional Rheometric Evaluationmentioning
confidence: 99%
“…Hyaluronic acid (HA), a naturally occurring glycosaminoglycan responsible for regulating viscoelastic properties of the vocal folds, 13 is a promising building block for tissue engineering of the vocal folds because of its innate biocompatibility and bioactivity. 14,15 This review will cover the application of HA in vocal fold tissue engineering. This review is organized into the following sections: vocal fold composition, vocal fold biomechanics, pathophysiology of vocal fold scarring with an emphasis on changes in HA, and current HA-based tissue engineering solutions for scarring.…”
Section: Introductionmentioning
confidence: 99%